Quantification of the uranium concentration in human urine by inductively coupled plasma-sector field mass spectrometry (ICP-SFMS) - Héctor Hernández-Mendoza; Estefanía Conde; Marta Fernández; Abel Yllera (Química Nova, 2013)
In this study, the validation of a method for analyzing the uranium (U) concentration in human urine samples by inductively coupled plasma-sector field mass spectrometry (ICP-SFMS) was conducted. PROCORAD (the Association for the Promotion of Quality Control in Radiotoxicological Analysis) provided two urine samples spiked with unknown contents of U (Sample A = 33.6 ± 1.0 µg/L and Sample B = 3.3 ± 0.1 µg/L) and one unspiked sample as a blank. The analyses were directly performed on the diluted urine samples (dilution factor = 1:20) in 5% v/v HNO3. The results obtained by ICP-SFMS corresponded well with the reference values, and the limits of detection were 235U = 0.049 × 10-3 µg/L and 238U = 7.37 × 10-3 µg/L. The ICP-SFMS technique has been shown to be successful in the analysis of the U concentration in human urine samples and for the quantification of isotopic ratios.